Methods of weed control on bean II - Vizeu, Luiz Antonio dos Santos; Ortolani, Antonio Francisco (Pesquisa Agropecuaria Brasileira, 2014)
During 1984, in Ipanema farm, Sorocaba, São Paulo State, Brazil, a field experiment was executed to compare the influence of methods of weed control on bean yield: cultivation with rottary tiller; cultivation with cultivator-shovel; cultivation with row cultivator (CRC) prototype nº 6, chemical control associated with cultivator-shovel; chemical control associated with CRC; and chemical control using preplant herbicide. The efficiency of each method and equipament was evaluated by percentage of controlled weeds, pulling bean plants and bean yields. The mechanical methods used separately were applied two times according to the need of culture and, when associated with chemical control, were applied one time at 35 days after seeding. The results were analyzed and showed that the mechanical methods used separately presented yield statistically lower than chemical control, chemical control associated with cuitivator-shovel and chemical control associated with CRC, in the area where 90% of the weeds were Brachiaria plantaginea (Link) Hitch.